Diabetes alters inflammation, angiogenesis, and fibrogenesis in intraperitoneal implants in rats - Oviedo-Socarrás, Teresa; Vasconcelos, Anilton C.; Barbosa, Irma X.; Pereira, Nubia B.; Campos, Paula P.; Andrade, Silvia P. (Microvascular research, 2014)
The increased prevalence of diabetes worldwide is associated with increasing numbers of diabetic individuals receiving synthetic matrices and biomedical implants to repair and/or replace biological tissues. This therapeutic procedure invariably leads to adverse tissue healing (foreign body reaction), thus impairing the biomedical device function of subcutaneous implants. However, the influence of diabetes on abnormal tissue healing in intraperitoneal implants is unclear. We investigated key components of foreign body reactions in diabetic rats. Polyether-polyurethane sponge discs were placed intraperitoneally in rats previously injected with streptozotocin for induction of diabetes and in non-diabetic rats. Implants removed 10days after implantation were assessed by determining the components of the fibrovascular tissue (angiogenesis, inflammation, and fibrogenesis). In implants from diabetic rats, fibrous capsule thickness and fibrovascular tissue infiltration (hematoxylin & eosin and picrosirius staining) were reduced in comparison with implants from non-diabetic rats. Hemoglobin (Hb) content (vascular index) and VEGF levels (pro-angiogenic cytokine) were increased after diabetes. However, the number of vessels (H&E and CD31-immunostaining) in the fibrovascular tissue from diabetic rats was decreased when compared with vessel numbers in implants from non-diabetic animals. Overall, all inflammatory parameters (macrophage accumulation-NAG activity; TNF-α and MCP-1 levels) increased in intraperitoneal implants after diabetes induction. The pro-fibrogenic cytokine (TGFβ-1) increased after diabetes, but collagen deposition remained unaltered in the implants from diabetic rats. These important diabetes-related changes (increased levels of pro-inflammatory and angiogenic and fibrogenic cytokines) in peritoneal implant healing provide an insight into the mechanisms of the foreign body response in the diabetic environment in rats. •The diabetic environment altered the healing response (foreign body reaction) in intraperitoneal implants.•Fibrous capsule thickness was reduced after diabetes.•Increased inflammation was observed in implants from diabetic rats.•Diabetes decreased angiogenesis, but implant blood flow and VEGF were increased.•Changes in collagen maturation were detected after diabetes.